Three new cave species of the subgenus Tachycines (Gymnaeta) (Orthoptera: Rhaphidophoridae: Aemodogryllinae) from northern Guizhou, China - Feng, Xueli; Huang, Shihui; Luo, Changqing (Zootaxa, 2020)
Some species of the subgenus Tachycines (Gymnaeta) are cavernicolous. In this paper, three new species of this subgenus, namely Tachycines (Gymnaeta) zaoshu sp. nov., Tachycines (Gymnaeta) shuangcha sp. nov., and Tachycines (Gymnaeta) tongrenus sp. nov., from karst caves in Guizhou Province, China are described. The results of this study expand our knowledge of the geographical distribution of the cave species of the subgenus Tachycines (Gymnaeta) in China. The morphological photographs of the three new cave species are provided.